A Study of Visual Programming Tools for the Open Source Project IoTivity - Yoo, Jae-Gon; Ma, MyungChul; Kim, Sangphil; Moon, Saemaro; Yoo, Jaeyoung; Choi, Yojin; Hong, Jin Yung; Kim, Jong-Bae (International Information Institute (Tokyo). Information, 2016)
Visual programming tools support the development of programs by modularization of program disposal procedures. This can raise productivity and stability as it makes it easy to intuitively understand the flow of a function or program that modules and parts have. It can even describe disposal procedures for data or algorithms. Meanwhile, one of the most important factors for a third-party company to consider when activating an IoT ecosystem is to add functionality by connecting the Internet to diverse manufactured products and to provide environments for smartphone applications or services. The purpose of this study is to develop IoTivity, an IoT open source project, to help developers use IoTivity, and to develop visual programming tools that enable ecosystem activation.